(untitled) (Educação e Pesquisa, 1999)
The paper presents references to better understand the implementation of changes at schools. Systematization of the references is based on a study about the reform of the Spanish education system and the implementation of a national curriculum in England and Wales, as well as on reviews of researches developed in that field. The reform of the Spanish education system attempted to balance the prescriptive character of the general guidelines with the more open approach of leaving each school to elaborate its own curricular proposal (taking into account its social context and the general guidelines). The study of the Spanish reform has contributed mainly to make explicit the diversity of viewpoints and attitudes that emerge within the context of an educational innovation. Such diversity is presented and summarized in the form of six different tensions. The implementation of the national curriculum in England and Wales aimed to establishing a greater control upon schools through a detailed and prescriptive curriculum, associated to the use of external exams as instruments of evaluating schools by the performance of their students in the exams. In this case, analyses are grounded on various research data. Those studies point to disastrous results in the educational context, with the impoverishment of pedagogical practices where activities targeted at the exams take priority. After using these two experiences to motivate the description of the references, the paper concludes by proposing that we should go beyond implementing innovations, toward processes of professional and institutional development that enable schools to produce proposals and contexts of change, and to interact critically with them.